2021
DOI: 10.5751/es-12141-260110
|View full text |Cite
|
Sign up to set email alerts
|

Toward an urgent yet deliberate conservation strategy: sustaining social-ecological systems in rangelands of the Northern Great Plains, Montana

Abstract: Urgency and deliberateness are often at odds when executing conservation projects, especially as the scale and complexity of objectives increases. The pace of environmental degradation supports immediate and measurable action. However, best practices for adaptive governance and building resilient social-ecological systems call for more deliberate efforts and participatory processes, which can be slow. We explore conflicts between urgency and deliberateness and the potential for their reconciliation through a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…We have shown that the greening of the NGP is driven by interactions between large‐scale vegetative shifts and cooccurring photosynthetic enhancement from established herbaceous vegetation. While recent WPE has contributed to enhanced C sequestration, WPE is also associated with a host of ecosystem and socio‐economic tradeoffs, including loss of grassland biodiversity, transformation of biogeochemical cycles, and changes to wildlife habitat (Barger et al, 2011; Epstein et al, 2021; Symstad & Leis, 2017; Wilcox et al, 2018). Furthermore, the combination of higher conifer densities and a warmer climate dramatically increases the probability of large wildfires (McWethy et al, 2019; Moritz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the greening of the NGP is driven by interactions between large‐scale vegetative shifts and cooccurring photosynthetic enhancement from established herbaceous vegetation. While recent WPE has contributed to enhanced C sequestration, WPE is also associated with a host of ecosystem and socio‐economic tradeoffs, including loss of grassland biodiversity, transformation of biogeochemical cycles, and changes to wildlife habitat (Barger et al, 2011; Epstein et al, 2021; Symstad & Leis, 2017; Wilcox et al, 2018). Furthermore, the combination of higher conifer densities and a warmer climate dramatically increases the probability of large wildfires (McWethy et al, 2019; Moritz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These shifts, trade‐offs, and asynchronies in vegetation phenology have feedbacks and consequences to ecological communities, including consumer–resource dynamics, species' behaviors, and other ecosystem processes (Beard et al., 2019 ; Morisette et al., 2009 ). Understanding the implications of future climate change is important for predicting potential ecological and social‐ecological impacts (e.g., Allstadt et al., 2015 ; Beard et al., 2019 ; Beever et al., 2019 ; Epstein et al., 2021 ; Hufkens et al., 2016 ). A collective understanding and consideration of multiple phenological measures and their drivers is important for effective management actions and continued development of a multiscale ecological perspective for management (Bezerra et al., 2019 ; Morisette et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Marking grazing lands as social‐ecological systems provides an opportunity to see interconnections among sub‐systems in agroecosystems that shape and constrain climate adaptation. For example, a growing body of research is looking at what makes these collaborative approaches successful, with a recognition that social, ecological, conservation, and climate adaptation goals on grazing lands are interconnected and interdependent (Brunson & Huntsinger, 2008; Epstein et al., 2021). Along with this, there is growing recognition of managers’ local ecological knowledge and long‐term management time frames, as well as increased engagement with Native Science and Traditional Ecological Knowledge (Elk, 2016) to understand rangeland management.…”
Section: Social Contexts For Adaptationmentioning
confidence: 99%